PENERAPAN MODEL PEMBELAJARAN THINK PAIRS SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SDN 010 SIARANGARANG KECAMATAN PUJUD KABUPATEN ROKAN HILIR - Mardawiyah, Mardawiyah; Kurniaman, Otang; Daud, Damanhuri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract, The problem this research is the students achievement of sains studies of state elementary school 010 Siarangarang fourth graders still low with an average value of 60 and minimum completeness criteria (KKM) sains studies is 75. Between students, amounting to 20 people only 25%, this research is Classroom Action Research (CAR), which aims to improve the student achievement of sains studies class III at of state elementary school 010 Siarangarang with implementation incuiri. Formulation of the problem : is the implementation incuirios sains students can improve students achievement of social studies at of state elementary school 010 Siarangarang. The research was conducted on Maret 03, 2015 to April 07, 2014 by 2 cycles. Subjects were students of of state elementary school 010 Siarangarang, totaling 20 people who use the data source. The data collection instruments in this thesis is a teacher and students activities sheets an students achievement. This thesis presents the results obtained each day before the action an improve in base score cycle with the average being 60. In the first cycle improve an average of 62 and an improve in the second with an average of 75. Activities of the teacher in the learning process in cycle of 58%, with increase big as 75% and the second meeting improve 89% and the second meeting improve 94%. Results of data analysis of students activities in the fisrt cycle with the fisrt meeting of an average of 53% and a second meeting improve to 67% and a second meeting improve to 75% at the first meeting of the second cycle with an average of 89%. However students achievement also increased the basic score of daily examonatoion as 40% which 8 students passed and 10 students failed. The ending of daily examonatoion as 80% which 16 students passed and 2 students failed.The Impemeltation Of Cooperative Learning Think Pairs Share (TPS) type, Resuts in the class III of state elementary school 010 Siarangarang that the implementation of incuiri of sains students can improve student achievement of sains studies at fourth graders of state elementary school 010 Siarangarang.Key Words : Model cooferative Learning Think Pairs Share (TPS) of sains students, fourth graders students Achievement